A kind of high bonding strength water-based wood glue powder and preparation method thereof

By adding modified nanotitanium dioxide and composite antibacterial agents to the preparation process of water-based wood glue powder, the existing water-based wood glue powder has been solved, and a longer service life and better adhesive performance have been achieved, ensuring the quality and grade of the product.

CN119019963BActive Publication Date: 2025-05-02GUANGZHOU YUANYE IND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411211260.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-05-02
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing water-based wood glue powder has poor antibacterial and mildew resistance, which leads to a shortened service life and poor bonding performance, affecting its quality and grade.

Method used

Using an improved preparation method, the antibacterial and anti-mold properties of wood glue powder are enhanced by adding modified nanotitanium dioxide and composite antibacterial agents during the reaction process, and their adhesive properties are improved through specific process steps and chemical reactions.

Benefits of technology

It significantly improves the antibacterial and anti-mold properties of water-based wood glue powder, extends its service life, and maintains excellent adhesive properties, ensuring its quality and grade.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020364290000101
    Figure BDA0005020364290000101
  • Figure BDA0005020364290000102
    Figure BDA0005020364290000102
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a water-based wood glue powder with high bonding strength and a preparation method thereof. In the invention, modified nano titanium dioxide is put into a DMF aqueous solution, and after being uniformly dispersed, a modifier and a grafting agent are added thereto, and the modifier and the grafting agent are bonded to the surface of the modified nano titanium dioxide through chemical bonds through a heat preservation reaction. Since the nano titanium dioxide itself has a porous structure and a large specific surface area, the content of the modifier and the grafting agent is significantly increased. Finally, the antibacterial property of the modified nano titanium dioxide is significantly enhanced under the synergistic effect of the modifier and the grafting agent. The prepared composite antibacterial agent is used as a raw material for preparing the water-based wood glue powder with high bonding strength, and its antibacterial and mildew-proof properties are significantly enhanced, and its service life is extended to a certain extent. In addition, the wood glue powder prepared by the invention also has excellent bonding performance, and its quality and grade are effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a high-bonding-strength water-based wood glue powder and a preparation method thereof. Background Art

[0002] Wood glue powder is made of powdered urea-formaldehyde resin, reinforcing agent and curing agent. Dissolve it in water before use, mix well and it can be widely used as adhesive in wood processing industry. It can be cold bonded or hot bonded. The glue has the characteristics of high bonding strength and easy preservation. It is widely used in furniture assembly, wood veneer, thin board lamination and wood board bonding.

[0003] A powdered urea-formaldehyde resin adhesive formula and its preparation process are disclosed in the patent document with application number "CN201410284282.2", and its ingredients mainly include: formaldehyde, urea, magnesium sulfate, sodium hydroxide, hydrochloric acid, alkali, ammonium chloride, and chrysanthemum water. The preparation process is: formaldehyde, ammonium chloride, urea, hydrochloric acid, alkali, sodium hydroxide and chrysanthemum water are mixed to adjust the purity, mixed and stirred continuously, and dried to obtain powdered urea-formaldehyde resin. Although the powdered urea-formaldehyde resin adhesive prepared by this patent document has the advantages of being non-flammable, good quality and low price. However, its own antibacterial and mildew-proof properties are relatively poor, which makes the antibacterial and mildew-proof properties of the board produced by it relatively poor, shortening its service life to a certain extent. Based on the above, the present invention provides a high bonding strength water-based wood glue powder and a preparation method thereof, which are used to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide a high bonding strength water-based wood glue powder and a preparation method thereof. The prepared wood glue powder not only has excellent antibacterial and mildew-proof properties, which prolongs its service life to a certain extent, but also has excellent bonding properties, effectively ensuring its quality and grade.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing water-based wood glue powder with high bonding strength, comprising the following steps:

[0007] Step 1, urea and 37wt% formaldehyde solution are put into a reaction device at a mass ratio of 1:1.5-2.0, polyvinyl alcohol with a mass of 0.6-1.2% of urea and anionic polyacrylamide with a mass of 0.8-1.5% are added thereto in sequence, the pH is adjusted to 7.8-8.3 after mixing and stirring evenly, and the mixture is kept warm at 65-70°C for 30-35min; after the reaction is completed, the temperature is raised to 85-90°C, and the reaction is kept warm for 30-35min, and the obtained reaction product is stored for standby use;

[0008] Step 2: first adjust the pH of the reaction product to 3.8-4.3 with a 10-12wt% ammonium chloride aqueous solution, and then adjust the pH to 7.3-7.8 with a potassium hydroxide aqueous solution and ammonia water; then add melamine with a mass of 10-15% of urea, mix and stir evenly, and then keep the mixture at a temperature of 70-75°C for 30-40 minutes;

[0009] Step 3: After the reaction is completed, adjust the pH of the resulting component to 7.8-8.3; then add 1.5-2.0% of the mass of the composite antibacterial agent to the resulting component, and homogenize at a rate of 10000-20000 r / min for 5-10 minutes; after the homogenization is completed, dry and crush in sequence to obtain high bonding strength water-based wood glue powder.

[0010] Preferably, in step 2, the concentration of the potassium hydroxide aqueous solution is 15-25 wt%, the concentration of the ammonia water is 20-25 wt%; and the volume ratio of the potassium hydroxide aqueous solution to the ammonia water is 1:4-6.

[0011] Preferably, the preparation method of the composite antibacterial agent comprises the following steps:

[0012] Step 1, ultrasonically disperse the pretreated nano titanium dioxide in toluene at a dosage ratio of 10 to 20 g / L, then add a silane coupling agent 3 to 5 times the mass of the pretreated nano titanium dioxide, mix and stir evenly, and then reflux for 8 to 10 hours; after the reaction is completed, filter the resulting components, wash with ethanol, and vacuum dry them in turn, and the final product is modified nano titanium dioxide;

[0013] Step 2: Add the modified nano titanium dioxide into a 40-60% DMF aqueous solution at a solid-liquid ratio of 10-15 g / L, and after uniform dispersion, add a modifier 4-6 times the mass of the modified nano titanium dioxide and a grafting agent 0.1-0.15 times the mass, and then keep the reaction at a temperature of 80-90°C for 20-25 hours; after the reaction is completed, separate the solid-liquid components of the obtained product, wash the obtained filter cake with deionized water and DMF for 2-3 times, and then dry it, and the final product is a composite antibacterial agent.

[0014] Preferably, the preparation method of the pretreated nano-titanium dioxide is as follows: adding nano-titanium dioxide into dioxane at a dosage ratio of 0.01 to 0.03 g / mL, and adding epichlorohydrin 4 to 6 times the mass of the nano-titanium dioxide and 0.5 to 0.8 times the mass of boron trifluoride ether thereto in sequence after ultrasonic dispersion, mixing evenly and keeping warm at 80 to 90° C. for 6 to 8 hours; after the reaction is completed, performing solid-liquid separation on the obtained product components, washing the filter cake with deionized water and ethanol for 2 to 3 times respectively and then drying it, and the obtained product is the pretreated nano-titanium dioxide.

[0015] The preparation method of porous nano titanium dioxide comprises the following steps: adding titanium isopropoxide into deionized water at a dosage ratio of 0.05 g / mL, then adding dodecyl dimethyl tertiary amine with a mass of 40% of titanium isopropoxide, adding hydrochloric acid aqueous solution with a mass of 35% of titanium isopropoxide and a concentration of 40wt% to the obtained mixed solution after ultrasonic dispersion, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 60 DEG C for 30 hours; after the reaction is completed, filtering the obtained product components, aging the obtained filter cake at a temperature of 120 DEG C for 35 hours, and then washing with methanol and vacuum drying in sequence to obtain porous nano titanium dioxide.

[0016] Preferably, the preparation method of the modifier is: add 1H-imidazole-1-propaneamine with a mass 3 to 4 times that of cyanamide to a 0.02 to 0.04 g / mL ethanol dispersion of cyanamide, add inorganic acid solution dropwise thereto after mixing and stirring evenly, and then keep the mixture at a temperature of 60 to 70° C. for 15 to 20 hours; after the reaction is completed, the reaction product is subjected to reduced pressure concentration, extraction and recrystallization treatment in turn, and the final product is the modifier.

[0017] Preferably, the inorganic acid solution is a 10-15 wt % hydrochloric acid aqueous solution, and its usage is 20-25% of the volume of ethanol.

[0018] Preferably, the preparation method of the grafting agent is: deionized water, chloroform and 5-methyl-2-isopropyl phenol are mixed and stirred evenly in a mass ratio of 1:0.3-0.4:0.4-0.6, and then 0.03-0.05 times the mass of lauroyl peroxide and 0.8-1.0 times the mass of 5-methyl-2-isopropyl phenol are added thereto respectively, and after mixing and stirring evenly, the temperature is raised to 45-55°C under the protection of nitrogen, and the reaction is stirred at this temperature for 10-15h; after the reaction is completed, the product components are rotary evaporated, and the remaining components are the grafting agent.

[0019] Preferably, the silane coupling agent is a mixture of 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane in equal amounts.

[0020] In a second aspect, the present invention provides a water-based wood glue powder with high bonding strength, which is prepared by the preparation method described above.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention uses cyanamide and 1H-imidazole-1-propaneamine as raw materials, the two react chemically in the environment of inorganic acid solution, and then successively undergo decompression concentration, extraction and recrystallization to finally prepare a modifier with high reactivity. Furthermore, the present invention uses 5-methyl-2-isopropylphenol and succinyl chloride imide as starting raw materials, the two react chemically under the action of lauroyl peroxide, and after the reaction is completed, a grafting agent is prepared by rotary evaporation. The prepared modifier and grafting agent are used for subsequent modification of nano titanium dioxide. In addition, the present invention uses nano titanium dioxide with a porous structure as a starting raw material, puts it into dioxane, and adds epichlorohydrin and boron trifluoride ether thereto successively after ultrasonic dispersion, realizes halogenation of nano titanium dioxide after chemical reaction, and obtains pre-treated nano titanium dioxide. The pretreated nano-titanium dioxide is ultrasonically dispersed in toluene, and then a silane coupling agent composed of 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane is added thereto. After reflux reaction, the resultant components are filtered, washed with alcohol and vacuum dried in sequence to finally obtain nano-titanium dioxide with 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane grafted on the surface, thereby introducing reactive groups to obtain modified nano-titanium dioxide.

[0023] Then the modified nano titanium dioxide is dropped into the DMF aqueous solution, and after being evenly dispersed, a modifier and a grafting agent are added thereto, and the modifier and the grafting agent are bonded to the surface of the modified nano titanium dioxide through a heat preservation reaction. Since the nano titanium dioxide itself has a porous structure and a larger specific surface area, the content of the modifier and the grafting agent is significantly increased. Finally, the antibacterial property of the modified nano titanium dioxide is significantly enhanced under the synergistic effect of the modifier and the grafting agent. The prepared composite antibacterial agent is used as the raw material for preparing the high bonding strength water-based wood glue powder, and its antibacterial and mildew-proof properties are significantly enhanced, and its service life is extended to a certain extent. In addition, the prepared wood glue powder of the present invention also has excellent bonding properties, and its quality and grade are effectively guaranteed. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A method for preparing water-based wood glue powder with high bonding strength comprises the following steps:

[0027] Step 1, urea and 37wt% formaldehyde solution are put into a reaction device at a mass ratio of 1:1.5, polyvinyl alcohol with a mass ratio of 0.6% of urea and anionic polyacrylamide with a mass ratio of 0.8% are added thereto in sequence, the pH is adjusted to 7.8 after mixing and stirring evenly, and the mixture is kept warm at 65°C for 30 minutes; after the reaction is completed, the temperature is raised to 85°C, and the reaction is kept warm for 30 minutes, and the obtained reaction product is stored for standby use;

[0028] Step 2: first adjust the pH of the reaction product to 3.8 with a 10wt% ammonium chloride aqueous solution, and then adjust the pH to 7.3 with a potassium hydroxide aqueous solution and ammonia water; then add melamine with a mass of 10% of urea, mix and stir evenly, and then keep the mixture at a temperature of 70°C for 30 minutes; wherein the concentration of the potassium hydroxide aqueous solution is 15wt%, the concentration of the ammonia water is 20wt%; and the volume ratio of the potassium hydroxide aqueous solution to the ammonia water is 1:4.

[0029] Step 3: After the reaction is completed, adjust the pH of the resulting component to 7.8; then add 1.5% of the mass of the composite antibacterial agent to the resulting component, and homogenize at a rate of 10,000 r / min for 5 minutes; after the homogenization is completed, dry and crush in sequence to obtain high bonding strength water-based wood glue powder.

[0030] The preparation method of the composite antibacterial agent comprises the following steps:

[0031] Step 1, ultrasonically disperse the pretreated nano titanium dioxide in toluene at a dosage ratio of 10 g / L, then add a silane coupling agent with a mass 3 times that of the pretreated nano titanium dioxide, mix and stir evenly, and reflux for 8 hours; after the reaction is completed, filter the resulting components, wash with ethanol, and vacuum dry them in turn, and the final product is modified nano titanium dioxide; wherein the silane coupling agent is a mixture of 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane in equal mass;

[0032] Step 2: Add the modified nano-titanium dioxide into a 40% DMF aqueous solution at a solid-liquid ratio of 10 g / L, and after uniform dispersion, add a modifier with a mass of 4 times that of the modified nano-titanium dioxide and a grafting agent with a mass of 0.1 times that of the modified nano-titanium dioxide, and then keep the reaction at 80°C for 20 hours; after the reaction is completed, separate the solid-liquid components of the obtained product, wash the obtained filter cake twice with deionized water and DMF respectively, and then dry it, and the final result is a composite antibacterial agent.

[0033] The preparation method of pretreated nano titanium dioxide is as follows: nano titanium dioxide is added into dioxane at a dosage ratio of 0.01 g / mL, and after ultrasonic dispersion, epichlorohydrin 4 times the mass of nano titanium dioxide and 0.5 times the mass of boron trifluoride ether are added in sequence, mixed evenly, and kept warm for reaction at 80°C for 6 hours; after the reaction is completed, the obtained product components are separated into solid and liquid, the filter cake is washed twice with deionized water and ethanol respectively, and then dried to obtain the pretreated nano titanium dioxide.

[0034] The preparation method of the modifier is as follows: add 1H-imidazole-1-propaneamine with a mass three times that of cyanamide to a 0.02g / mL ethanol dispersion of cyanamide, add inorganic acid solution dropwise thereto after mixing and stirring evenly, and then keep the mixture warm at 60°C for 15 hours; after the reaction is completed, carry out reduced pressure concentration, extraction and recrystallization treatment on the reaction product in turn, and the final product is the modifier; wherein the inorganic acid solution is a 10wt% hydrochloric acid aqueous solution, and its amount is 20% of the volume of ethanol.

[0035] The preparation method of the grafting agent is as follows: deionized water, chloroform and 5-methyl-2-isopropylphenol are mixed and stirred evenly in a mass ratio of 1:0.3:0.4, and then 0.03 times the mass of lauroyl peroxide and 0.8 times the mass of 5-methyl-2-isopropylphenol are added thereto respectively, and after mixing and stirring evenly, the temperature is raised to 45°C under the protection of nitrogen, and the reaction is stirred at this temperature for 10 hours; after the reaction is completed, the product components are rotary evaporated, and the remaining components are the grafting agent.

[0036] Example 2

[0037] The preparation method of a high bonding strength water-based wood glue powder provided in this embodiment is basically the same as that in Example 1, except that: the preparation method of the composite antibacterial agent used in the high bonding strength water-based wood glue powder is different. The specific preparation method of the composite antibacterial agent in this embodiment is as follows:

[0038] The preparation method of the composite antibacterial agent comprises the following steps:

[0039] Step 1, ultrasonically disperse the pretreated nano titanium dioxide in toluene at a dosage ratio of 15g / L, then add a silane coupling agent with a mass 4 times that of the pretreated nano titanium dioxide, mix and stir evenly, and reflux for 10 hours; after the reaction is completed, filter the resulting components, wash with ethanol, and vacuum dry them in turn, and finally obtain modified nano titanium dioxide; wherein the silane coupling agent is a mixture of 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane in equal mass;

[0040] Step 2: Add the modified nano-titanium dioxide into a 50% DMF aqueous solution at a solid-liquid ratio of 12 g / L, and after uniform dispersion, add a modifier 5 times the mass of the modified nano-titanium dioxide and a grafting agent 0.12 times the mass of the modified nano-titanium dioxide, and then keep the reaction at 85°C for 25 hours; after the reaction is completed, separate the solid-liquid components of the obtained product, wash the obtained filter cake with deionized water and DMF for 3 times, and then dry it, and the final result is a composite antibacterial agent.

[0041] The preparation method of pretreated nano titanium dioxide is as follows: nano titanium dioxide is added into dioxane at a dosage ratio of 0.02 g / mL, and after ultrasonic dispersion, epichlorohydrin 5 times the mass of nano titanium dioxide and boron trifluoride ether 0.6 times the mass of nano titanium dioxide are added in sequence, mixed evenly, and kept warm for reaction at 85°C for 7 hours; after the reaction is completed, the obtained product components are separated into solid and liquid, the filter cake is washed with deionized water and ethanol for 3 times respectively, and then dried, and the obtained product is pretreated nano titanium dioxide.

[0042] The preparation method of the modifier is as follows: add 1H-imidazole-1-propaneamine whose mass is 3 times that of cyanamide to a 0.03g / mL ethanol dispersion of cyanamide, add inorganic acid solution dropwise thereto after mixing and stirring evenly, and then keep the mixture warm at 65°C for 20 hours; after the reaction is completed, carry out reduced pressure concentration, extraction and recrystallization treatment on the reaction product in turn, and the final product is the modifier; wherein the inorganic acid solution is a 15wt% hydrochloric acid aqueous solution, and its amount is 25% of the volume of ethanol.

[0043] The preparation method of the grafting agent is as follows: deionized water, chloroform and 5-methyl-2-isopropylphenol are mixed and stirred evenly in a mass ratio of 1:0.35:0.5, and then 0.04 times the mass of lauroyl peroxide and 0.8 times the mass of 5-methyl-2-isopropylphenol are added thereto respectively, and after mixing and stirring evenly, the temperature is raised to 50°C under the protection of nitrogen, and the reaction is stirred at this temperature for 15 hours; after the reaction is completed, the product components are rotary evaporated, and the remaining components are the grafting agent.

[0044] Example 3

[0045] The preparation method of a high bonding strength water-based wood glue powder provided in this embodiment is basically the same as that in Example 1, except that: the preparation method of the composite antibacterial agent used in the high bonding strength water-based wood glue powder is different. The specific preparation method of the composite antibacterial agent in this embodiment is as follows:

[0046] The preparation method of the composite antibacterial agent comprises the following steps:

[0047] Step 1, ultrasonically disperse the pretreated nano titanium dioxide in toluene at a dosage ratio of 20g / L, then add a silane coupling agent with a mass 5 times that of the pretreated nano titanium dioxide, mix and stir evenly, and reflux for 10 hours; after the reaction is completed, filter the resulting components, wash with ethanol, and vacuum dry them in turn, and finally obtain modified nano titanium dioxide; wherein the silane coupling agent is a mixture of 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane in equal mass;

[0048] Step 2: Add the modified nano-titanium dioxide into a 60% DMF aqueous solution at a solid-liquid ratio of 15 g / L, and after uniform dispersion, add a modifier with a mass of 6 times that of the modified nano-titanium dioxide and a grafting agent with a mass of 0.15 times that of the modified nano-titanium dioxide, and then keep the reaction at 90°C for 25 hours; after the reaction is completed, separate the solid-liquid components of the obtained product, wash the obtained filter cake with deionized water and DMF for 3 times, and then dry it, and the final result is a composite antibacterial agent.

[0049] The preparation method of pretreated nano titanium dioxide is as follows: nano titanium dioxide is added into dioxane at a dosage ratio of 0.03 g / mL, and after ultrasonic dispersion, epichlorohydrin with a mass 6 times that of the nano titanium dioxide and boron trifluoride ether with a mass 0.8 times that of the nano titanium dioxide are added in sequence, and after mixing evenly, the mixture is kept warm at 90°C for 8 hours; after the reaction is completed, the obtained product components are separated into solid and liquid, and the filter cake is washed with deionized water and ethanol for 3 times respectively and then dried to obtain the pretreated nano titanium dioxide.

[0050] The preparation method of the modifier is as follows: add 1H-imidazole-1-propaneamine with a mass 4 times that of cyanamide to a 0.04g / mL ethanol dispersion of cyanamide, add inorganic acid solution dropwise thereto after mixing and stirring evenly, and then keep the mixture warm at 70°C for 20 hours; after the reaction is completed, carry out reduced pressure concentration, extraction and recrystallization treatment on the reaction product in turn, and the final product is the modifier; wherein the inorganic acid solution is a 15wt% hydrochloric acid aqueous solution, and its amount is 25% of the volume of ethanol.

[0051] The preparation method of the grafting agent is as follows: deionized water, chloroform and 5-methyl-2-isopropylphenol are mixed and stirred evenly in a mass ratio of 1:0.4:0.6, and then 0.05 times the mass of lauroyl peroxide and 1.0 times the mass of 5-methyl-2-isopropylphenol are added thereto respectively, and after mixing and stirring evenly, the temperature is raised to 55°C under the protection of nitrogen, and the reaction is stirred at this temperature for 15 hours; after the reaction is completed, the product components are rotary evaporated, and the remaining components are the grafting agent.

[0052] Comparative Example 1

[0053] The difference between this embodiment and embodiment 1 is that in this embodiment, an equal amount of a modifier is used instead of a grafting agent.

[0054] Comparative Example 2

[0055] The difference between this embodiment and embodiment 1 is that in this embodiment, an equal amount of grafting agent is used to replace the modifier.

[0056] Performance Testing

[0057] The wood glue powder samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 were mixed with water of 0.5 times the mass thereof; wherein the water was added in two batches, two-thirds of the total water volume was added in the first batch, and one-third of the total water volume was added in the second batch. After adding water, the mixture was stirred at a speed of 150 r / min for 5 minutes until the glue solution was evenly mixed, and then the prepared glue solution was applied to the composite board processing technology;

[0058] Among them, the specific processing technology of composite panels is as follows:

[0059] Step 1: Use a peeling machine to peel the wood into 1.6mm thick slices, and then send them into a hot air furnace to dry them until the moisture content is 8% to obtain wood veneer;

[0060] Step 2: Use a glue sprayer to spray the prepared glue on the surface of the wood veneer, with a single-sided glue coating of 180g / m 2 ; The 9 layers of wood veneers are hot-pressed and bonded together according to the principle that the textures of adjacent layers of wood veneers are perpendicular to each other; the hot-pressing temperature is 125°C, the pressure is 4.2Mpa, and the holding time is 35min;

[0061] Step 3: The plate obtained in the second step is naturally cooled to room temperature, and then statically pressed and aged for 24 hours at a pressure of 1.2 MPa to obtain a composite plate.

[0062] The relevant properties of the composite board samples prepared by using the adhesive provided in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the test results were recorded in Table 1; the damage value classification standard is shown in Table 2.

[0063] Table 1 Performance test results

[0064]

[0065] Table 2 Classification criteria of damage value

[0066]

[0067]

[0068] By comparing and analyzing the relevant data in the table, it can be seen that the prepared wood glue powder not only has excellent antibacterial and mildew-proof properties, which prolongs its service life to a certain extent, but also has excellent bonding properties, effectively ensuring its quality and grade. This shows that the high bonding strength water-based wood glue powder and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0069] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing water-based wood glue powder with high bonding strength, characterized in that: The following steps are involved: Step 1, urea and 37wt% formaldehyde solution are put into a reaction device at a mass ratio of 1:1.5-2.0, polyvinyl alcohol with a mass of 0.6-1.2% of urea and anionic polyacrylamide with a mass of 0.8-1.5% are added thereto in sequence, the pH is adjusted to 7.8-8.3 after mixing and stirring evenly, and the mixture is kept warm at 65-70°C for 30-35min; after the reaction is completed, the temperature is raised to 85-90°C, and the reaction is kept warm for 30-35min, and the obtained reaction product is stored for standby use; Step 2: first adjust the pH of the reaction product to 3.8-4.3 with a 10-12wt% ammonium chloride aqueous solution, and then adjust the pH to 7.3-7.8 with a potassium hydroxide aqueous solution and ammonia water; then add melamine with a mass of 10-15% of urea, mix and stir evenly, and then keep the mixture at a temperature of 70-75°C for 30-40 minutes; Step 3, after the reaction is completed, the pH of the resulting component is adjusted to 7.8-8.3; then, 1.5-2.0% of the composite antibacterial agent by weight is added to the resulting component, and homogenized at a rate of 10000-20000 r / min for 5-10 minutes; after the homogenization is completed, the high bonding strength water-based wood glue powder is obtained by drying and crushing in sequence; The preparation method of the composite antibacterial agent comprises the following steps: Step 1, ultrasonically disperse the pretreated nano titanium dioxide in toluene at a dosage ratio of 10 to 20 g / L, then add a silane coupling agent 3 to 5 times the mass of the pretreated nano titanium dioxide, mix and stir evenly, and then reflux for 8 to 10 hours; after the reaction is completed, filter the resulting components, wash with ethanol, and vacuum dry them in turn, and the final product is modified nano titanium dioxide; Step 2: Add the modified nano titanium dioxide into a 40-60% DMF aqueous solution at a solid-liquid ratio of 10-15 g / L, and add a modifier 4-6 times the mass of the modified nano titanium dioxide and a grafting agent 0.1-0.15 times the mass of the modified nano titanium dioxide respectively after being evenly dispersed, and then keep the reaction at a temperature of 80-90° C. for 20-25 hours; after the reaction is completed, separate the solid-liquid components of the obtained product, wash the obtained filter cake with deionized water and DMF for 2-3 times, and then dry it, and the final product is a composite antibacterial agent; The preparation method of the pretreated nano titanium dioxide is as follows: adding nano titanium dioxide into dioxane at a dosage ratio of 0.01 to 0.03 g / mL, uniformly dispersing by ultrasonication, sequentially adding epichlorohydrin 4 to 6 times the mass of the nano titanium dioxide and boron trifluoride ether 0.5 to 0.8 times the mass of the nano titanium dioxide, mixing uniformly, and heat-retaining and reacting at a temperature of 80 to 90° C. for 6 to 8 hours; after the reaction is completed, performing solid-liquid separation on the obtained product components, washing the filter cake with deionized water and ethanol for 2 to 3 times respectively, and then drying the filter cake, and obtaining the pretreated nano titanium dioxide; The preparation method of the modifier is as follows: add 1H-imidazole-1-propaneamine whose mass is 3 to 4 times of that of cyanamide to a 0.02 to 0.04 g / mL ethanol dispersion of cyanamide, add inorganic acid solution dropwise thereto after mixing and stirring evenly, and then keep the mixture at a temperature of 60 to 70° C. for 15 to 20 hours; after the reaction is completed, carry out reduced pressure concentration, extraction and recrystallization treatment on the reaction product in sequence, and the final product is the modifier; The preparation method of the grafting agent is as follows: deionized water, chloroform and 5-methyl-2-isopropylphenol are mixed and stirred evenly in a mass ratio of 1:0.3-0.4:0.4-0.6, and then 0.03-0.05 times of lauroyl peroxide and 0.8-1.0 times of succinyl chloride imide are added thereto respectively, and after mixing and stirring evenly, the temperature is raised to 45-55° C. under the protection of nitrogen, and the reaction is stirred at this temperature for 10-15 hours; after the reaction is completed, the resultant components are rotary evaporated, and the remaining components are the grafting agent.

2. The method for preparing a high bonding strength water-based wood glue powder according to claim 1, characterized in that: In the step 2, the concentration of the potassium hydroxide aqueous solution is 15-25wt%, and the concentration of the ammonia water is 20-25wt%; and the volume ratio of the potassium hydroxide aqueous solution to the ammonia water is 1:4-6.

3. The method for preparing a high bonding strength water-based wood glue powder according to claim 1, characterized in that: The inorganic acid solution is a 10-15wt% hydrochloric acid aqueous solution, and its usage is 20-25% of the volume of ethanol.

4. The method for preparing a high bonding strength water-based wood glue powder according to claim 1, characterized in that: The silane coupling agent is prepared by mixing 3-glycidylpropyltrimethoxysilane and 3-aminopropyltrimethoxysilane in equal amounts.

5. A water-based wood glue powder with high bonding strength obtained according to the method for preparing a water-based wood glue powder with high bonding strength according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Powdery urea-formaldehyde resin adhesive formula and preparation process thereof

    CN104073204A

  • Preparation method of multi-functional synergetic anti-oxidative stabilizer for sulfide bond linked urea

    CN104529875A

  • Novel ENF-grade environment-friendly adhesive manufacturing process

    CN117004355A